Attitudes of Liver Transplant Candidates Toward Organs From Increased‐Risk Donors. Issue 6 (21st May 2019) - Humar, Sapna S.; Liu, Jingqian; Pinzon, Natalia; Kumar, Deepali; Bhat, Mamatha; Lilly, Les; Selzner, Nazia
Abstract : Increased‐risk donor (IRD) organs make up a significant proportion of the deceased organ donor pool but may be declined by patients on the waiting list for various reasons. We conducted a survey of patients awaiting a liver transplant to determine the factors leading to the acceptance of an IRD organ as well as what strategies could increase the rate of acceptance. Adult liver transplant candidates who were outpatients completed a survey of 51 questions on a 5‐point Likert scale with categories related to demographics, knowledge of IRDs, and likelihood of acceptance. A total of 150 transplant candidates completed the survey (age 19‐80 years). Male patients constituted 67.3%. Many patients (58.7%) had postsecondary education. Only 23.3% of patients had a potential living donor, and 58/144 (40.3%) were not optimistic about receiving an organ in the next 3 months. The overall IRD organ acceptance rate was 41.1%, whereas 26.2% said they would decline an IRD organ. Women were more likely to accept an IRD organ (54.3% versus 34.7%; P = 0.02). Those who had a college education or higher tended to have lower IRD organ acceptability (28.3% versus 47.4%; P = 0.07). Acceptability also increased as the specified transmission risk of human immunodeficiency virus or hepatitis C virus decreased ( P < 0.001). Patients were also more likely to accept an IRD organ if they were educated on the benefits of IRD organs (eg, knowledge that an IRD organ was of better quality increased overall acceptance from 41.1% to 63.3%; P < 0.001). Our survey provides insight into liver transplant candidates who would benefit from greater education on IRD organs. Strategies targeting specific educational points are likely to increase acceptability.